Pendekatan Cepat Memahami Kitab Ikhtisor Nahwiyyah : Dari Menghafal Menuju Pemahaman di Madrasah Diniyyah Al-Amiriyyah - M. Maulana Rizqi Abadi (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This research is based on the existence of problems in Arabic grammar which are often considered complicated by many students in general and especially in Madrasah Diniyyah Al-Amiriyyah. This research aims to improve students' understanding of the book of Ikhtisor Nahwiyyah (Nahwu) through an active approach of memorization without memorization. This approach is designed so that students can not only remember the term or rule, but also understand the meaning and context of the lesson. The method used in this study is qualitative descriptive by using data collection methods, observations, interviews, and questionnaires that function to evaluate students' understanding of the material. The study involved 35 students for 40 days. The results of the study show that students have experienced a significant increase in understanding the basic concepts of Nahwu science, as well as being able to apply them in daily learning. This approach facilitates students to be actively involved in the learning process, so that they not only memorize but also understand the contents of the book in depth. This method is expected to be a reference for educators to develop more effective learning strategies in religious education, so that it can improve the quality of education and experience at Madrasah Diniyyah Al-Amiriyyah and thus, this study proves that the memorization method without memorization can be an effective strategy.